2001
DOI: 10.1080/109158101753252992
|View full text |Cite
|
Sign up to set email alerts
|

Trichloroethylene, Trichloroacetic Acid, and Dichloroacetic Acid: Do They Affect Fetal Rat Heart Development?

Abstract: Trichloroethylene (TCE), trichloroacetic acid (TCA), and dichloroacetic acid (DCA) are commonly found as groundwater contaminants in many regions of the United States. Cardiac birth defects in children have been associated with TCE, and laboratory studies with rodents report an increased incidence of fetal cardiac malformations resulting from maternal exposures to TCE, TCA, and DCA. The objective of this study was to orally treat pregnant CDR(CD) Sprague-Dawley rats with large bolus doses of either TCE (500 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 27 publications
4
62
1
Order By: Relevance
“…In well-designed and -conducted studies using experimental techniques recognized by regulatory agencies as useful for identifying developmental hazards, rats, mice, and rabbits have been exposed to TCE by inhalation at up to 1800 ppm (Schwetz et al, 1975;Dorfmueller et al, 1979;Beliles et al, 1980;Healy et al, 1982;Zablotny et al, 2002), rats have been exposed to t-DCE by inhalation at up to 12,000 ppm (Hurtt et al, 1993), and rats have been treated by gavage at 500 mg TCE/kg/day (Fisher et al, 2001). None of these studies found any suggestion of exposurerelated developmental toxicity, even in the presence of maternal toxicity.…”
Section: Laboratory Studiesmentioning
confidence: 98%
See 2 more Smart Citations
“…In well-designed and -conducted studies using experimental techniques recognized by regulatory agencies as useful for identifying developmental hazards, rats, mice, and rabbits have been exposed to TCE by inhalation at up to 1800 ppm (Schwetz et al, 1975;Dorfmueller et al, 1979;Beliles et al, 1980;Healy et al, 1982;Zablotny et al, 2002), rats have been exposed to t-DCE by inhalation at up to 12,000 ppm (Hurtt et al, 1993), and rats have been treated by gavage at 500 mg TCE/kg/day (Fisher et al, 2001). None of these studies found any suggestion of exposurerelated developmental toxicity, even in the presence of maternal toxicity.…”
Section: Laboratory Studiesmentioning
confidence: 98%
“…None of these studies found any suggestion of exposurerelated developmental toxicity, even in the presence of maternal toxicity. None of these studies found any evidence of specific cardiac teratogenicity, even when (Fisher et al, 2001) the microdissection technique of Dawson et al (1990Dawson et al ( , 1993 was used and a member of that research group was part of the study team.…”
Section: Laboratory Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The discrepancy may be explained by two major differences in the exposure protocols used by the authors: In the Dawson et al study, rats were exposed to TCE via drinking water, as opposed to gavage (Fisher et al, 2001). Additionally, in Dawson's protocol the dams were exposed to the toxicant starting at day 0 of conception (with a regimen of 7 days/week exposure), whereas Fisher's study started the exposure at day 6, and used a regimen of 5 days/week.…”
Section: Introductionmentioning
confidence: 91%
“…Human exposure to TCE through contaminated drinking water has been associated with a 3-fold increase in congenital heart malformations in children born to exposed mothers . Animal studies have confirmed that TCE, and its metabolites DCE (dichloroethylene) and TCAA are specific cardiac teratogens in chicks and rats (Dawson et al, 1990(Dawson et al, , 1993Goldberg et al, 1990Goldberg et al, , 1992Johnson et al, 1998), although some controversy still exists stemming from a study reporting no significant teratogenic effects of TCE in rat embryonic heart (Fisher et al, 2001).…”
Section: Introductionmentioning
confidence: 93%